1 + 1 9 1 9 8 ( 1 0 1 − 1 ) + 1 9 2 9 8 ( 1 0 2 − 1 ) + 1 9 3 9 8 ( 1 0 3 − 1 ) + … = ?
Give your answer to three decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You need to check your working again. It should be 8 1 1 5 7 .
Log in to reply
oops, that was a mistype.
@Pi Han Goh Yep the answer is 8 1 1 5 7
The first term is 0, not 1
S = 1 + 1 9 1 9 8 ( 1 0 1 − 1 ) + 1 9 2 9 8 ( 1 0 2 − 1 ) + . . .
= 1 + 9 8 n = 0 ∑ ∞ 1 9 n 1 0 n − 1
= 1 + 9 8 n = 0 ∑ ∞ [ 1 9 n 1 0 n − 1 9 n 1 ]
= 1 + 9 8 [ 1 − 1 9 1 0 1 − 1 − 1 9 1 1 ]
S = 8 1 1 5 7 ≈ 1 . 9 3 8
Problem Loading...
Note Loading...
Set Loading...
S = 1 + 1 9 8 + 1 9 2 8 8 + 1 9 3 8 8 8 + . . .
1 9 S = 1 9 1 + 1 9 2 8 + 1 9 3 8 8 + . . .
This implies that you have:
1 9 1 0 S = 1 9 1 0 + 1 9 2 8 0 + 1 9 3 8 8 0 + . . . = 1 9 1 0 + ( 1 9 2 8 8 + 1 9 3 8 8 8 + . . . ) − ( 1 9 2 8 + 1 9 3 8 + . . . )
1 9 1 0 S = 1 9 1 0 + ( S − 1 9 2 7 ) − 1 7 1 4 ⟹ S = 8 1 1 5 7 ≈ 1 . 9 3 8